Status Harta Bersama Suami Kedua dalam Pembagian Waris Menurut Hukum Islam: Studi Yuridis-Empiris di Kota Bima - Susanti, Susi; Muh. Yunan Putra,; Hikmah, (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2025)
The division of joint property in a second marriage often generates legal disputes when one spouse passes away. This study aims to analyze the status of joint property of the second husband in inheritance distribution under Islamic law and to examine the practices implemented in the local community of Bima City. The research employed a juridical-empirical method with a descriptive-analytical approach, combining interviews, field observations, and literature review. The findings reveal that the community in Tambana, Jatiwangi Subdistrict, predominantly applies customary inheritance practices, namely family deliberation and equal distribution among heirs. Such practices contradict the provisions of Islamic inheritance law, which stipulates fixed and detailed shares (faraidh) that are considered qath‘i (definitive). The primary factors behind this deviation include limited understanding of Islamic inheritance principles, lack of awareness of the legal status of joint property, and the strong influence of local traditions transmitted across generations. This study highlights the urgency of socializing Islamic inheritance law and strengthening the role of marital agreements as preventive measures against disputes over property distribution. The research contributes to enriching the juridical discourse on harmonizing Islamic law and customary practices in inheritance cases in Indonesia.